ON THE HISTORY OF THE PREPARATION OF THE MOSCOW COMMUNIST CONFERENCES (NOVEMBER, 1957). Y. V. ANDROPOV AND B. N.PONOMAREV’S MISSION TO BELGRAD - A. S. Stykalin (Гуманитарные и юридические исследования)
The source, which is published here, reveals the motives of the rejection of the Communist Union of Yugoslavia to support the Declaration of the communist conference (November, 1957) in Moscow - the important program document aimed at the consolidation of international communist movement after the crisis of 1956.